Batasan pertanggungjawaban pidana koperasi atas tidak berwenangnya debitur terhadap barang gadainya - Hartarto Pakpahan (Jurnal Cakrawala Hukum, 2020)
In the practice of credit services distributed by cooperatives to members as well as to the community, cooperatives typically require a special guarantee in the form of movable objects (pawning) with the intention, if the debtor defaults on his credit, the creditor can take repayment of the right of collection from the pledge object. In practice it also turns out that often the debtor is not authorized to pledge mortgages as collateral for loans to the pawnshop cooperative as the creditor. Debtor is not authorized for these pawns usually because the pawned item is a loan item (belonging to a third party), that is, the safekeeping item or even the pawning item is the result of theft / confiscation / crime (obtained by illegal means) so that the cooperative that receives the item as collateral for credit, become involved in a legal problem, namely criminal offense as referred to in Article 480 of the Criminal Code. Whereas on the other hand there are weaknesses on the evidence of ownership of a movable object which is the object of a pledge, that is as stipulated in article 1977 of the Indonesian Civil Code which states "who controls the movable object is considered to be the owner." Cooperative criminal liability for the pledge that he receives when the pawning goods provided by the debtor are obtained in an illegal manner.How to cite item: Pakpahan, H. (2020). Batasan pertanggungjawaban pidana koperasi atas tidak berwenangnya debitur terhadap barang gadainya. Jurnal Cakrawala Hukum, 11(2), 166-176. doi:https://doi.org/10.26905/idjch.v11i2.4395